К характеристике американской норкп (Mustela vison Sсhr.) о. Сахалина - Беньковский, Л.М. (Вестник зоологии, 1971)
For the first time in native literature the hybrid Mustela vison S с h r. from Sakhalin Is described. Dimensions weight and some interior indices as well as the content of
vitamin A, micro- and macroelements, fat in the liver and muscular tissue of the bodyare given in comparison with the analogous data in some other representatives of the
AU'.stelidae family from Sakhalin.